L’interaction en classe, un “polylogue praxéologique”? - Bouchard, Robert (Studia Romanica Posnaniensia, 2007)
This study focuses on classroom interaction during a geography lesson for 2nd year students in a French Secondary School. It deals with two phenomena: (i) the multi-participant organisation of this interaction; (ii) its task-oriented nature. In the turn, two issues are raised on the one hand, the role played in the interaction by the context of work with its written and pictorial artefacts and^ on the other hand, the various types of activities carried out by the teachers and the students. The teacher is the only one who knows the ultimate aim of the communicative event which he has planned with precision beforehand in a written form and which he effectuates through successive stages by presenting documents used to channel the students’ participation. This leads to students’ participating in diverse tasks which are not only didactic but furthermore (micro-)social. The synchronisation between the teacher’s acts and those of the students is ensured through the (ethno-) methods developed during their previous school experience and is specifically materialised, in a recurrent way, into the form of ternary pedagogical exchanges.